Teacher Burnout and Self-Efficacy: A Contemporary Perspective from Secondary Education - Mahnoor Tariq; Sanila Kanwal; Nazia Tabassum; Sadia Hameed; Azra Jamil (Indus Journal of Social Sciences, 2025)
Background: Teachers burnout is a growing problem that contributes to a low level of well-being and a lack of conviction in teachers in their potential to help students learn (Saloviita and Pakarinen, 2021). It is necessary to understand the impact of burnout on the self-efficacy of teachers to enhance teaching quality and academic success of students. Aim of the study: The aim of the study was to examine the impact of teacher burnout on self-efficacy of teacher in secondary level. Procedure: It was a quantitative study using cross-sectional survey design and the convenience technique was used to sample the 100 secondary level teachers in Rawalpindi. They have been requested to complete 21-item Teacher Burnout Scale (Friedland et al., 1986) and 10-item Teacher Self-efficacy Scale (Schwarzer and Jerusalem, 1995) to be able to share their experience better. The analysis of data was done using SPSS-21. Results: Pearson correlation was used to analyze the data based on the significant results of the analysis on associaation between burnout and self-efficacy, further analysis were done to study the effect of burnout on self-efficacy. The regression result showed that burnout is a strong predictor of self-efficacy in secondary level teachers i.e; increased burnout diminished self-efficacy and hampered the teachers in performing their functions. Conclusion: The article concludes that teacher burnout has an adverse effect on teacher self-efficacy, meaning that the more the teacher is exhausted emotionally and physically, the less confidence he or she has in coping with the classroom requirements. The results of the study show that there is a necessity of institutional support mechanisms to diminish burnout and enhance the feeling of professional competence in teachers.